Heliocentric in the Qur'an: A Comparative Study of Tafsir Jalalain and Tafsir Ilmi of the Ministry of Religion of the Republic of Indonesia - Opi Yensi; Laksamana Naufal Hadi; Kharismah Gulsani (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2026)
The Qur'an contains many scientific cues that encourage humans to contemplate Allah's creation, including the phenomenon of the circulation of celestial bodies. One of the verses that is often studied in this context is Q.S. Yasin verses 38–40, which mentions the motion of the sun and moon on their respective circular lines. This verse is often associated with the theory of heliocentrism in modern astronomy, which states that the sun is the center of the solar system and the earth revolves around it. In the tradition of interpretation, the meaning of the verse develops according to the scientific context of each era. This study aims to examine and compare the interpretation of Q.S. Yasin verses 38–40 in Tafsir Jalalain as a representation of classical interpretation and Tafsir Ilmi of the Ministry of Religion of the Republic of Indonesia as a contemporary science-oriented interpretation. The research uses a qualitative method based on library research. The results of this study show that Tafsir Jalalain interprets the verse literally and theocentrically, while the Tafsir Ilmi of the Ministry of Religion of the Republic of Indonesia associates it with modern astronomy. The two do not affirm each other, but reflect the epistemological dynamics of interpretation that make the Qur'an always relevant throughout the ages.